Assessing the Impact of Posterior Leaf Spring Ankle Foot Orthosis on Knee Joint of Hemiplegic Stroke Patients Through Software Gait Analysis - Soran Abdulrahman , Mahmood; Husni Ali , Ghassan (Diyala Journal of Medicine, 2023)
Background: Ankle Foot Orthoses (AFO) is mostly advised for a stroke patient who is complicated with plantarflexion deformity, to support and improve the alignments of the feet for reducing knee joint extension and promoting hip joint extension through stance-phase. Objective: To provide deeper knowledge using software gait analysis for the biomechanical effects of PLS AFO for stroke patients. Patients and Methods: We divided 42 participants into 3 groups (the first and second groups were 28 stroke participants that used AFO and with OUT-AFO and the third group was 14 normal participants without deformity. All participants walk 10 meters in a straight line for the same time their gait was captured at Comfortable Walking Speed (CWS). Temporal-spatial and kinematic parameters of the knee joint were compared in the study. Results: The PLS AFO showed improvement in knee ROM in the AFO condition that has better knee flexion in the early stance (from 8.16 to 16.24 degrees in the AFO condition), a huge increase in the late stance of knee extension (from 0.16 to 3.82 degrees) and better knee flexion than the barefoot condition in the swing flexion (from 26.1 to 39.78 degrees). Also, the mean Time Up and Go (TUG) identically decreased in stroke participants (from 36.04 s in OUT-AFO to 22.6 s in AFO condition). Conclusion: In this study, we showed that using a PLS AFO can be beneficial for improving knee ROM and progress walking speed, gait symmetry, balance, and reducing the risk of falls.